Attribution of Air Temperature Variation to the Incidence of COVID‐19 - Rui Wang; Jianping Huang; Xinbo Lian; Han Li; Yingjie Zhao; Beidou Zhang; Dongliang Han (Geophysical Research Letters, 2025)
Abstract COVID‐19 incidence exhibits periodic fluctuations, and recurring waves of infection could lead to large‐scale future outbreaks. Air temperature is a key factor influencing COVID‐19 transmission, but in‐depth research on its specific mechanisms and quantitative effects remains limited. This study investigates temperature‐COVID‐19 relationships using 412,167 daily cases from China's 31 provinces (2020–2022). Results demonstrate that both sustained cold and rapid cooling significantly elevate transmission risks, with distinct regional thresholds: when temperatures fall below 3.15°C (North), 0.55°C (Northeast), 16.39°C (East), 9.38°C (Central), 13.39°C (Southwest), and −5.56°C (Northwest) accompanied by respective drops of >0.32, >0.67, >0.12, >2.12, >1.42, and >1.55°C, outbreak risks surge. Cold conditions directly drove 88.06% of cases, while temperature drops accounted for 59.33%. The highest relative risk of COVID‐19 incidence due to extreme low temperatures can reach 4.53. This study addresses gaps in understanding temperature‐COVID‐19 relationships and provides evidence to guide targeted epidemic control strategies during adverse weather conditions.